2021
DOI: 10.1515/ntrev-2021-0073
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms, influencing factors, and applications of electrohydrodynamic jet printing

Abstract: E-jet printing is a micro- and nano-manufacturing technique that utilizes electric field-induced fluid jet printing for achieving better control and resolution than traditional jet printing processes. In addition to high printing resolution, E-jet printing has advantages in some aspects such as wide material applicability, which has been successfully applied in numerous applications that include sensors, transistors, tissue engineering scaffolds, and photonic devices. This article reviews the electrohydrodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 198 publications
0
14
0
Order By: Relevance
“…When the electric field is applied, the solution overcomes its surface tension, and the jet is ejected from the needle. Due to the charge deposited on each droplet and solvent evaporation, the jet breaks up into smaller charged droplets collected on the stainless steel substrate [ 195 ].…”
Section: Processing Methodsmentioning
confidence: 99%
“…When the electric field is applied, the solution overcomes its surface tension, and the jet is ejected from the needle. Due to the charge deposited on each droplet and solvent evaporation, the jet breaks up into smaller charged droplets collected on the stainless steel substrate [ 195 ].…”
Section: Processing Methodsmentioning
confidence: 99%
“…If the jetting speed matches the moving speed of X-Y stage (or needle), a straight cone jet is generated. When the jetting speed is higher than the moving speed of the X-Y stage (or needle), wavy filaments are produced [80]. Previous studies found the line width of EHD filament decreased with the increase of the moving speed of the X-Y stage (or needle) [92,98], while He et al gave the opposite result [99].…”
Section: Process Parametersmentioning
confidence: 96%
“…A slight increase in voltage based on dripping mode, a micro dripping mode can be obtained with a much smaller size than the nozzle. Unlike the dripping mode, the pulsating jet mode does not shrink the meniscus after the droplets are separated [80]. A pulsating mode is formed by a slight increase in voltage or flow rate.…”
Section: Ehd Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…The most disseminated ones are piezoelectric and thermal inkjet printing, nonetheless, there are other methods whose popularity is increasing and can also grant high-quality printing of functional inks [36]. Among those, electrohydrodynamic (EHD)-IJP [37][38][39], aerosol jet printing [40], drop impact printing [41], and acoustic printing [42], can be highlighted.…”
Section: Inkjet Printing Of Functional Inks 21 Inkjet Printing Processmentioning
confidence: 99%